Karakterisasi dan Identifikasi Senyawa Metabolit Sekunder dari Bakteri yang Bersimbion dengan Ascidia gemmata - Nuryanti Rumalolas; Rina Anita Mogea; Maria Massora (Jurnal Penelitian Pendidikan IPA, 2023)
Isolation of secondary metabolites from bacteria that have a symbiont with Ascidians has been shown to have enormous potential. This study aims to identify the types of secondary metabolites in Bacillus sp. which has a symbiont with A. gemmata. The research was carried out using laboratory experimental methods by means of phytochemical screening. After testing, the results of the characterization of bacteria that lead to the genus Bacillus and the secondary metabolites contained are alkaloid compounds